Is Same-Day Discharge Following Minimally Invasive Sacrocolpopexy Safe and Feasible? A National Contemporary Database Analysis. Issue 7 (3rd July 2022) - Raju, Rubin; Hanson, Kristine T.; Habermann, Elizabeth B.; Occhino, John A.; Linder, Brian J.
Abstract : Objective: The aim of this study was to investigate trends and outcomes of ambulatory minimally invasive sacrocolpopexy (MISC) using data from a contemporary multicenter nationwide cohort. Methods: We used the American College of Surgeons National Surgical Quality Improvement Program database to identify women who underwent nonemergent MISC (laparoscopic and robotic) from 2012 to 2018. Exclusion criteria were age <18 or ≥90 years, rectal prolapse, postoperative discharge day ≥3, and concomitant hysterectomy, transvaginal mesh repair, colpocleisis, and/or colorectal surgery. Baseline demographics and 30-day outcomes were compared between patients who underwent same-day discharge (SDD; discharge on postoperative day [POD] 0) and those discharged on POD 1–2 using Kruskal-Wallis, Fisher exact, and Pearson χ 2 tests. A 2-sided Cochran-Armitage trend test assessed SDD over time, and person-years methodology was used to assess readmission rates. Multivariable logistic regression and Cox proportional hazards modeling evaluated associations between SDD and postoperative outcomes. We hypothesized that SDD increased over the study time frame and is not associated with adverse outcomes. Results: Of 2, 928 women, 362 (12.4%) were SDD, and 2, 566 (87.6%) were discharged POD 1–2. The proportion of SDD nearly quadrupled over time (5.6% [2012], 20.6% [2018]; P < 0.001). The SDD group was younger (mean age, 61.9 vs 63.6; P = 0.04), with lower proportion of American Society of Anesthesiologists class III or higher (21.8% vs 27.5%; P = 0.02) and hypertension (37.3% vs.46.5%; P < 0.001), shorter total operation time (median, 142 vs 172 minutes; P < 0.001), and fewer concomitant slings (21.5% vs 33.0%; P < 0.001). Outcomes were similar for SDD: 30-day overall complications (3.0% vs 4.4%; P = 0.23), readmissions (1.1% vs 2.0%; P = 0.28), and reoperations (1.1% vs 0.9%; P = 0.55) and persisted with multivariable analysis. Conclusion: Ambulatory MISC significantly increased during the study period and appears safe and feasible in select patients.